Perception of graduates about the education of Nursing Technicians - Gabriel Luiz Nascimento Fioramonte; Adriana Avanzi Marques Pinto; Maria José Sanches Marin (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to interpret the perception of graduates from the nursing technician program on the learning process developed during their education. Methods: a qualitative study was conducted from March to September 2021, based on interviews with 20 graduates from a nursing technician program at a school in the Midwest of São Paulo, using thematic analysis and the NVivo tool. Results: the following themes were identified: traditional teaching methods, active learning strategies, valuing proactivity and experiences in professional practice. Final Considerations: according to the graduates, the teaching process is essentially based on traditional methods, although there are initiatives to implement active strategies and recognition of the importance of advancing student proactivity and practical experience.